The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.5455/msm.2013.25.250-254
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Culturally Competent Communication in Health Care in the Republic of Macedonia

Abstract: Aim:To examine the existing situation, barriers and consequences of the intercultural communication in health institutions and to offer training models for strengthening and improving communication skills of health professionals in the Republic of Macedonia.Methods:A cross-sectional survey was conducted to assess the relationship between patients and health professionals. A total of 813 health professionals (302 physicians and 511 other medical staff) from different healthcare institutions, and 1016 patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Additionally, clinicians may exhibit less empathy toward patients of diverse races and ethnic backgrounds and those belonging to low socioeconomic status (Roberts et al, 2021). In the Pollozhani et al (2013) study conducted in North Macedonia, every third patient who was examined believed that his or her doctor or other medical staff did not understand his or her feelings and did not have the answers to all of his or her inquiries. Migrants and minorities living in a country may face linguistic and cultural challenges to accessing certain healthcare services, such as health promotion facilities, screening services, and specialized care, increasing their risk of poor health status due to a lack of (suitable) care (Dauvrin et There are significant issues related to the healthcare services offered to non-dominant cultures in European contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clinicians may exhibit less empathy toward patients of diverse races and ethnic backgrounds and those belonging to low socioeconomic status (Roberts et al, 2021). In the Pollozhani et al (2013) study conducted in North Macedonia, every third patient who was examined believed that his or her doctor or other medical staff did not understand his or her feelings and did not have the answers to all of his or her inquiries. Migrants and minorities living in a country may face linguistic and cultural challenges to accessing certain healthcare services, such as health promotion facilities, screening services, and specialized care, increasing their risk of poor health status due to a lack of (suitable) care (Dauvrin et There are significant issues related to the healthcare services offered to non-dominant cultures in European contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified barriers to intercultural communication such as lack of understanding of different cultures, ethnocentrism, and stereotyping, and ways to overcome these barriers 19,36–38 . Several authors have focused on aspects of effective intercultural communication such as personality, cultural self‐efficacy, cultural intelligence, and other language‐specific skills 39–42 . One unique study by Paternotte et al 43 attempted to view intercultural communication through the eyes of the patients by questioning patients about their preferences and experiences regarding intercultural communication in the healthcare setting.…”
Section: Uses Of the Conceptmentioning
confidence: 99%
“…In contrast, one rural Australian medical school found relatively high levels of confidence on self-reported intercultural competence scales 19 but this varies across countries and between genders. 20 There are many frameworks and models describing the key elements in cultural competency education 4,9,21,22,23 . Common elements include awareness of world view, knowledge of other cultures, adaptability, appreciation of language differences, and awareness of personal biases.…”
Section: Introductionmentioning
confidence: 99%